Rethinking the religious factor in foreign policy - Toropova, Maria (Springer VS, 2021)
"The authors of this book analyze the mechanisms and strategies that allow specific religious actors to affect the foreign policy agenda and decisions of the countries in which they are active. Paying special attention to events and phenomena that have had a decisive impact on regional and global development, this book provides an international outlook on how the activities of religious actors can influence foreign policy. The research subject was inspired by the idea of identifying what dynamics are occurring and whether there are any discernible trends"--Back cover
Keywords: Aufsatzsammlung; Einfluss; Religion; Außenpolitik